Information System for Sales and Ordering of Ornamental Fish at Rusdy Aquarium in Bulukumba Regency Based on a Website - Ferdiansah Ferdiansah; Husni Sulaiman; Sri Asfirawati Halik (Institut Teknologi dan Bisnis Bina Adinata, 2025)
This study aims to design a sales and ordering information system at Rusdy Aquarium online using a website, to implement a sales and ordering information system at Rusdy Aquarium using a website. The research method used in this study is a software development method known as Software Development Life. Cycles (SDLC). The Waterfall method is the earliest SDLC approach used for software development. The sequence in the Waterfall Method is serial, starting from the process of requirements analysis and definition, system and software design, implementation and unit testing, integration and system testing, and operation and maintenance of the system. The results showed that the information system for selling and ordering ornamental fish at the Rusdhy aquarium in Bulukumba district is website-based, in its design the system uses data flow diagrams (DFD), namely data flow diagrams, context diagrams, programming languages ​​used PHP, Javascript, MySQL as base storage. the data, and the laravel framework, nuxtjs, as well as the integration of payment gateways midtrans and shipping costs king onkir and testing is carried out using the black box method, testing uses the System Usability Scale (SUS) method with a value of 75 which means grade scale C or is included in the Good category which This means that the website-based information system for selling and ordering ornamental fish at Rusdy Aquarium in Bulukumba Regency can be used easily by its users.